Hubungan Beban Kerja dan Burnout terhadap Perilaku Caring Perawat di Ruang Rawat Inap RS “X” - Muh Taufik Saddam; Yeny Sulistyowati; Thika Marliana (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Nurses' caring behavior is a fundamental element in quality healthcare services. However, pressures such as high workload and burnout can hinder its implementation. This study aims to analyze the relationship between workload and burnout on the caring behavior of nurses in the Inpatient Ward of “X” Hospital. The research method used is quantitative with a cross-sectional design, involving 96 practicing nurses through a total sampling technique. Data were collected using the Subjective Workload Assessment Technique (SWAT) questionnaire, the Maslach Burnout Inventory (MBI), and a caring behavior questionnaire based on Jean Watson's theory. The results showed that the workload (p<0.001) and burnout (p<0.001) variables have a significant negative relationship with caring behavior. Logistic regression analysis identified workload as the more dominant factor influencing caring behavior. Simultaneously, these two independent variables could explain 57.9% of the variance in nurses' caring behavior. This study concludes that an increase in workload and burnout levels significantly decreases nurses' caring behavior, making workload management a priority intervention to improve the quality of nursing care.